2015
DOI: 10.1166/jbn.2015.2024
|View full text |Cite
|
Sign up to set email alerts
|

Local Administration of Gold Nanoparticles Prevents Pivotal Pathological Changes in Murine Models of Atopic Asthma

Abstract: Although gold nanoparticles have been shown to exhibit a range of beneficial biological properties, including antiinflammatory and anti-oxidant effects, their putative impact on allergic asthma has not been addressed. In this study, we evaluated the potential of nasal-instilled gold nanoparticles to prevent allergen-induced asthma in distinct murine models of this disease. Swiss-Webster (outbred) and A/J (inbred) mice were sensitized with ovalbumin and then treated with intranasal injections of gold nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 0 publications
1
33
0
Order By: Relevance
“…There are two previous conflicting studies about the local effects of gold nanoparticles applied to the respiratory tract of asthmatic mice. Barreto et al investigated the effect of 12 nm citrated gold nanoparticles on an OVA asthma model in Swiss‐Webster and A/J mice and found that gold nanoparticle treatment reduced OVA‐induced inflammation and airway hyperresponsiveness, similar to our results . In the second study, Hussain et al used 40 nm citrated gold nanoparticles in toluene diisocyanate (TDI)‐induced asthma in BALB/c mice and reported that both the inflammation and airway hyperresponsiveness increased due to gold nanoparticle treatment .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…There are two previous conflicting studies about the local effects of gold nanoparticles applied to the respiratory tract of asthmatic mice. Barreto et al investigated the effect of 12 nm citrated gold nanoparticles on an OVA asthma model in Swiss‐Webster and A/J mice and found that gold nanoparticle treatment reduced OVA‐induced inflammation and airway hyperresponsiveness, similar to our results . In the second study, Hussain et al used 40 nm citrated gold nanoparticles in toluene diisocyanate (TDI)‐induced asthma in BALB/c mice and reported that both the inflammation and airway hyperresponsiveness increased due to gold nanoparticle treatment .…”
Section: Resultssupporting
confidence: 84%
“…Therefore, PEG‐coated (PEGylated) gold nanoparticles were the focus of this study. However, to ensure comparability with previous toxicological studies, we also studied citrated gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Gold NPs are known for their application as biosensors and gene delivery vehicles, and in general for their anti‐inflammatory and antioxidant effects . Intranasal administration of gold NPs prior to allergen challenge inhibited accumulation of inflammatory cells, mucus production, airway hyperreactivity, and production of pro‐inflammatory cytokines and reactive oxygen species in OVA‐sensitized mice . Magnetic NPs combine the advantage of good detectability for imaging purposes and drug delivery and gained attention, for example, in hyperthermia‐based therapy .…”
Section: Nonbiodegradable Nanostructuresmentioning
confidence: 99%
“…In the study by Hussain et al discussed above, Au NPs were also used in their TDI-induced asthma model and were found to be even more inflammatory than TiO NPs, showing increased AHR and total BALF cell 2 counts. In the OVA asthma model, Au NPs have been found to actually decrease OVA-induced allergy as seen by decreased inflammatory cell lung accumulation, decreased mucus production and lower cytokine levels (Barreto et al, 2015). Similarly, both PEGylated and citrated Au NPs have been shown to attenuate OVA-induced inflammation: both types of Au NPs decreased AHR, total BALF cell counts and eosinophil numbers (Omlor et al, 2017).…”
Section: Gold Nanoparticlesmentioning
confidence: 98%